Acoustic accelerometry reveals diel activity patterns in premigratory Port Jackson sharks. Issue 16 (27th July 2019) - Kadar, Julianna; Ladds, Monique; Mourier, Johann; Day, Joanna; Brown, Culum
Abstract: Distinguishing the factors that influence activity within a species advances understanding of their behavior and ecology. Continuous observation in the marine environment is not feasible but biotelemetry devices provide an opportunity for detailed analysis of movements and activity patterns. This study investigated the detail that calibration of accelerometers measuring root mean square (RMS) acceleration with video footage can add to understanding the activity patterns of male and female Port Jackson sharks ( Heterodontus portusjacksoni ) in a captive environment. Linear regression was used to relate RMS acceleration output to time‐matched behavior captured on video to quantify diel activity patterns. To validate captive data, diel patterns from captive sharks were compared with diel movement data from free‐ranging sharks using passive acoustic tracking. The RMS acceleration data showed captive sharks exhibited nocturnal diel patterns peaking during the late evening before midnight and decreasing before sunrise. Correlation analysis revealed that captive animals displayed similar activity patterns to free‐ranging sharks. The timing of wild shark departures for migration in the late breeding season corresponded with elevated diel activity at night within the captive individuals, suggesting a form of migratory restlessness in captivity. By directly relating RMS acceleration output to activity level, we show that sex, time of day, and sex‐specific seasonal behavior all influenced activity levels. This study contributes to a growing body of evidence that RMS acceleration data are a promising method to determine activity patterns of cryptic marine animals and can provide more detailed information when validated in captivity. Abstract : In order to distinguish the factors that influence Port Jackson shark movement, we tagged wild sharks with accelerometers and observed them in captivity. We confirmed that acoustic accelerometers can be calibrated to provide more detailed information. We also found that the captive sharks displayed a nocturnal diel pattern that was comparable to their wild counterparts.